Copper(II) and the pathological H50Q α-synuclein mutant: Environment meets genetics. Issue 1 (2nd January 2017) - Villar-Piqué, Anna; Rossetti, Giulia; Ventura, Salvador; Carloni, Paolo; Fernández, Claudio O.; Outeiro, Tiago Fleming
ABSTRACT: Copper is one of the metals described to bind the Parkinson disease-related protein α-synuclein (aSyn), and to promote its aggregation. Although histidine at position 50 in the aSyn sequence is one of the most studied copper-anchoring sites, its precise role in copper binding and aSyn aggregation is still unclear. Previous studies suggested that this residue does not significantly affect copper-mediated aSyn aggregation. However, our findings showed that the aggregation of the pathological H50Q aSyn mutant is enhanced by copper hints otherwise. Despite the inexistence of a model for aSyn H50Q-copper complexation, we discuss possible mechanisms by which this metal contributes to the misfolding and self-assembly of this particular aSyn mutant. Considering the genetic association of the H50Q mutation with familial forms of Parkinson disease, and the fact that copper homeostasis is deregulated in this disorder, understanding the interplay between both factors will shed light into the molecular and cellular mechanisms triggering the development and spreading of the aSyn pathology.